Involvement of seminal leukocytes, reactive oxygen species, and sperm mitochondrial membrane potential in the DNA damage of the human spermatozoa. (19th January 2015) - Lobascio, A. M.; De Felici, M.; Anibaldi, M.; Greco, P.; Minasi, M. G.; Greco, E.
Summary: Measurement of reactive oxygen species (ROS) producing leukocytes in semen has been a standard component of the semen analysis, but its true significance remains still unknown. In this study, we have correlated the number of seminal leukocytes to various semen parameters. We found a negative correlation between the leukocyte number and sperm concentration ( r s = −0.22; p = 0.01) and motility ( r s = −0.20; p = 0.02). In contrast, a positive correlation between the number of leukocytes and both seminal ROS ( r s = 0.70, p < 0.001; n = 125) and the number of spermatozoa with DNA fragmentation ( r s = 0.43, p = 0.032; n = 25) was found. However, only a trend of positive correlation between ROS and the number of spermatozoa with TUNEL‐detected DNA fragmentation was observed. Moreover, this latter was not correlated with loss of sperm mitochondrial membrane potential (MMP) (10% vs 35%, r s = 0.25, p = 0.08; n = 50). Overall these results indicate that the presence of high number of leukocytes in the ejaculate negatively affects key semen parameters, as sperm concentration and motility, associated with infertility conditions. Moreover, they suggest that leukocytes are the major source of the seminal ROS and cause of sperm DNA fragmentation. However, the absence of a clear correlation between ROS and sperm DNA fragmentation, and spermatozoa with damaged DNA and MMP loss, suggest that ROS produced by leukocytes might be not the only cause of DNA damage in spermatozoa and that intrinsic mitochondrial‐dependent apoptotic pathways might not have a major impact on sperm DNA fragmentation.